The Economic Consequences of Fiscal Rules - Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2023)
Fiscal rules are controversial. They mitigate politicians' flexibility in responding to shocks and pursuing expansionary fiscal policy. They help, however, to handle politicians' commitment problem in fiscal policies. I portray the new and fast growing empirical literature in public economics that examines the economic consequences of fiscal rules. The survey encompasses the literature on fiscal rules at the national, sub-national and local level. The results show that fiscal rules reduce budget deficits, public spending and borrowing costs and increase GDP growth. The results do not suggest that fiscal rules decrease public investment. Future research should examine in more detail the unintended effects of fiscal rules such as how they relate to creative accounting.
Keywords: H50; H60; H70; N10; O10; R10; 330; fiscal rules